DIFFERENCES IN THE EFFECTIVENESS OF HEALTH PROMOTION MEDIA BETWEEN LEAFLET AND POWERPOINT ON THE LEVEL OF ADOLESCENTS' KNOWLEDGE ABOUT HIV/AIDS - Na'im, Zaitun; Nurjanah, Nunung; Nurfita, Nisa Rizki; ,, Tonasih (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
The high number of HIV/AIDS infections that continue to increase, especially among young people or teenagers, makes this a serious problem. Therefore, efforts are needed to increase adolescent knowledge about HIV/AIDS, one of which is through health promotion. The purpose of this study was to determine the difference in the effectiveness of health promotion media between leaflets and powerpoint on the level of adolescent knowledge about HIV/AIDS at SMA YABAKII 2 Gandrungmangu Cilacap. The research method used was pre-experimental with a two-group pre-test post-test design. Sampling with a total sampling of 116 respondents. Based on the results of the study, the average knowledge after being given health promotion about HIV/AIDS with leaflet media was 18.05 while with powerpoint media it was 18.60. The Mann Whitney test results obtained a p-value of 0.028 smaller than 0.05 (0.028 0.05) which means there is a difference in the effectiveness of health promotion media between leaflets and powerpoint. The use of powerpoint media is more effective than leaflet to increase adolescent knowledge about HIV/AIDS at SMA YABAKII 2 Gandrungmangu Cilacap. It is hoped that health workers will contribute more to health promotion in schools so that they can reduce HIV/AIDS cases in Indonesia.